DEVIASI PRINSIP KESANTUNAN DALAM KOMUNIKASI LISAN SISWA SMAN 2 KENDARI: ANALISIS PRAGMATIK - Gege, Muhammad Yazid Abd. Rachim; Marshinta, Marshinta; Maliuddin, Maliuddin (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
This research aims to analyze in-depth the deviations of linguistic politeness principles manifested in the oral communication of students at Sekolah Menengah Atas Negeri (SMAN) 2 Kendari through the lens of pragmatic analysis, grounded in Leech's politeness principle theoretical framework. Employing spontaneous conversation data from students in grades X, XI, and XII, collected through audio recording and verbatim transcription methods, this qualitative study identifies and classifies various forms of deviations from the maxims of politeness. The research findings indicate that the phenomenon of politeness principle deviation occurs quite frequently in verbal interactions among students, potentially leading to negative impacts on the quality of social relationships and the conduciveness of the learning environment at school. Furthermore, this research has implications for providing practical insights for educators in formulating learning strategies that explicitly emphasize the urgency of polite and ethical communication, as well as enhancing students' metacognitive awareness regarding the pragmatic consequences of their language choices in building and maintaining positive social interactions.